2020
DOI: 10.3390/ijgi9030183
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Analysis of Intense Convective Storms Tracks in a Densely Urbanized Italian Basin

Abstract: Intense convective storms usually produce large rainfall volumes in short time periods, increasing the risk of floods and causing damages to population, buildings, and infrastructures. In this paper, we propose a framework to couple visual and statistical analyses of convective thunderstorms at the basin scale, considering both the spatial and temporal dimensions of the process. The dataset analyzed in this paper contains intense convective events that occurred in seven years (2012–2018) in the Seveso-Olona-La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…For flood impacts reduction, convective spells need to be monitored. In fact, as shown by Sangiorgio and Barindelli [63], long-lasting convective cells present a higher probability of generating hydrometeorological risks. Events containing such convective spells produced very important rainfall.…”
Section: Discussionmentioning
confidence: 89%
“…For flood impacts reduction, convective spells need to be monitored. In fact, as shown by Sangiorgio and Barindelli [63], long-lasting convective cells present a higher probability of generating hydrometeorological risks. Events containing such convective spells produced very important rainfall.…”
Section: Discussionmentioning
confidence: 89%
“…Hitchcock et al (2021) also studied the characteristics of linear precipitation systems and their contributions in heavy rainfall over Melbourne by applying an object-based approach over a weather radar data near Melbourne. Similar object-based radar studies have been conducted in Sydney (Potts et al 2000), Southeast Queensland (Peter et al 2015) and other parts of the world such as Germany (Thomassen et al 2020), Italy (Sangiorgio and Barindelli 2020) and Spain (Rigo et al 2010). This technique has also been applied over satellite datasets to study the global climatology of different storm types (Nesbitt et al 2000;Jiang et al 2011;Wall et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…The effect of adding an input parameter, on the extreme rainfall event multiclass classification, was inspected by Sangiorgio et al [17] They compared the performance of logistic regression and DNN with weather parameters as inputs and found that with the addition of an input parameter selected by them, there was an improvement in the accuracy of the classification. Many researchers have used parameters derived from the GNSS and radar for analysis [18], classification [8], and nowcasting [6] of the rainfall, storms, thunderstorms. The parameters derived from GNSS include zenith tropospheric delay (ZTD) [8], [17], precipitable water vapor [11], [19], [20], IWV [21], and IWV with vertical profiles of wet refractivity [6], to name a few.…”
Section: Introductionmentioning
confidence: 99%